2019
DOI: 10.3390/cancers11122012
|View full text |Cite
|
Sign up to set email alerts
|

Breast-Associated Adipocytes Secretome Induce Fatty Acid Uptake and Invasiveness in Breast Cancer Cells via CD36 Independently of Body Mass Index, Menopausal Status and Mammary Density

Abstract: Breast adiposity is correlated with body mass index, menopausal status and mammary density. We here wish to establish how these factors influence the cross-talk between breast adipocytes and normal or malignant breast cells. Adipocyte-derived stem cells (ASCs) were obtained from healthy women and classified into six distinct groups based on body mass index, menopausal status and mammary density. The ASCs were induced to differentiate, and the influence of their conditioned media (ACM) was determined. Unexpecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 60 publications
4
34
0
Order By: Relevance
“…We have found that intratumoral adipocyte-high breast cancer enriched for the inflammation, metastasis, and cancer stemness related gene sets, which is in agreement with the previous reports [25,[49][50][51][52]. This was more significant with the ER+/HER2-subtype compared with TNBC.…”
Section: Discussionsupporting
confidence: 92%
“…We have found that intratumoral adipocyte-high breast cancer enriched for the inflammation, metastasis, and cancer stemness related gene sets, which is in agreement with the previous reports [25,[49][50][51][52]. This was more significant with the ER+/HER2-subtype compared with TNBC.…”
Section: Discussionsupporting
confidence: 92%
“… [ 63 ] Luminal A Co-culture model (MCF-7) Proliferation, migration and invasion were increased in BC cells, which was most prominent for the highly invasive SUM159 cells and, to a lesser extent, for the less invasive MCF7 cells. [ 78 ] TNBC Co-culture model (SUM159) Not-given Human invasive breast carcinoma sample Collagen reorganization at the tumor-adipose periphery, as well as the positive relevance between PAI-1 and PLOD2 were found in invasive breast carcinoma, revealing a new stromal collagen network that favors tumor invasion and metastasis establish between BC cells and surrounding adipocytes at the tumor invasive front. [ 80 ] TNBC Co-culture model (MDA-MB-231, Hs578t) Adipocytes and adipocyte-derived conditioned media, but not pre-adipocytes, caused the mesenchymal MDA-MB-231 and Hs578t cells to form significantly more epithelial-like structures when compared to the typical stellate colonies formed in control 3D cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor lipid metabolism is regulated not only by genetic and epigenetic changes in the tumor cells but also by the availability of lipids provided by tumor-surrounding adipocytes. Zaoui et al showed that mammary adipocytes potentiated the invasiveness of BC cells and the number of lipid droplets in adipocyte cytoplasm, which were mediated by metabolic reprogramming via CD36-mediated exogenous fatty acid uptake [78]. Wang et al reported the function of the JAK/STAT3 pathway in regulating lipid metabolism, once inhibiting JAK/STAT3 would lead to the block of diverse lipid metabolic gene expression, including CPT1B that encoded the critical enzyme for FAO [25].…”
Section: Metabolic Reprogrammingmentioning
confidence: 99%
“…Several studies have shown alterations in the expression of enzymes involved in lipid metabolism [ 42 , 43 , 44 ]. Additionally, metabolomics study of the microenvironment of tumor cells have shown that after interaction with breast cancer cells, cancer-associated adipocytes reprogram their metabolism involving upregulation of almost all macronutrients—carbohydrates, lipids, and amino acids [ 45 , 46 ]. Conversely, limited research on lipidomics of breast cancer is available and even fewer studies have addressed TNBC, although altered lipid metabolism represents a well-established hallmark of cancer development.…”
Section: Mass Spectrometry-based Omics In Tnbcmentioning
confidence: 99%